2011
DOI: 10.1074/jbc.m110.183699
|View full text |Cite|
|
Sign up to set email alerts
|

Ursolic Acid, a Pentacyclin Triterpene, Potentiates TRAIL-induced Apoptosis through p53-independent Up-regulation of Death Receptors

Abstract: Discovery of the molecular targets of traditional medicine and its chemical footprints can validate the use of such medicine. In the present report, we investigated the effect of ursolic acid (UA), a pentacyclic triterpenoid found in rosemary and holy basil, on apoptosis induced by TRAIL. We found that UA potentiated TRAIL-induced apoptosis in cancer cells. In addition, UA also sensitized TRAIL-resistant cancer cells to the cytokine. When we investigated the mechanism, we found that UA down-regulated cell surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(47 citation statements)
references
References 54 publications
3
43
0
1
Order By: Relevance
“…However, Prasad et al (2010) claim that the ursolic acid (a pentacyclic terpene) induced the formation of reactive oxygen species (ROS) and promoted apoptosis in a tumour-derived cell strain. The same effects were observed using other pentacyclic terpenes, such as asiatic acid (Park et al, 2005) and betulinic acid (Wick et al, 1999).…”
Section: Resultsmentioning
confidence: 98%
“…However, Prasad et al (2010) claim that the ursolic acid (a pentacyclic terpene) induced the formation of reactive oxygen species (ROS) and promoted apoptosis in a tumour-derived cell strain. The same effects were observed using other pentacyclic terpenes, such as asiatic acid (Park et al, 2005) and betulinic acid (Wick et al, 1999).…”
Section: Resultsmentioning
confidence: 98%
“…This indicates that PA induces apoptosis through the death receptor-induced extrinsic pathway. Recently, triterpenoids such as celastrol and ursolic acid have been suggested to potentiate tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis through upregulation of DR4 and/or DR5 (16,17). In our previous study, 3-O-acetyloleanolic acid was also shown to induce apoptosis in HCT-116 cells, which is mediated by upregulation of DR5 (18).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies including ours [1] have confirmed the anti-growth ability of ursolic acid against a number of human cancer cells [2][3][4][5]. In addition, ursolic acid has showed a broad spectrum of activities to influence cancer progression and development, including interfering tumorigenesis, metastasis and angiogenesis, and inducing tumor cell apoptosis and differentiation [3][4][5].…”
Section: Introductionmentioning
confidence: 87%